Democratic Republic of Sao Tome and Principe : 2016 Article IV Consultation, First Review under the Extended Credit Facility, and Request for Waiver for Nonobservance of Performance Criterion and Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Exective Director for the Democratic Republic of Sao Tome and Principe. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses recent economic developments and economic outlook and risks of Sao Tome and Principe. Although Sao Tome and Principe's economic development is constrained by its insularity, fragility, limited resources, and low capacity as a small island state, this African country has made commendable progress toward greater macroeconomic stability. GDP growth has averaged more than 4 percent per year since 2012, faster than many small islands states, but not sufficiently strong and diversified to meaningfully improve economic prospects and reduce poverty significantly. The forthcoming presidential election, with the risk of extra budgetary spending and continued weakness in the banking sector, are the main sources of short-term risks to the economic outlook.